VALUE OF PERMANENT CROPS IN THE GROSS VALUE ADDED IN AGRICULTURE - Grujić Vučkovski, Biljana; Vukićević, Ksenija; Stevanović, Dragana (Journal of Agricultural Sciences (Belgrade), 2024)
The aim of the research is to analyze the impact of the value of the production of permanent crops (fruit and viticulture sector) on the realized gross value added (abbr. GVA) in agriculture in Serbia and the EU from 2012 to 2022. The results were obtained by applying a multiple regression model where the dependent variable is GVA in agriculture, and the independent variables represent the production values ​​of the fruit and viticulture sector (in EUR mln). The coefficients of the model were tested using the t-test, and the model was verified using the F-test at a significant level of 0.05. The value of the standardized beta coefficient showed that the fruit growing sector has a greater influence on the realized GVA of agriculture in Serbia and the EU (0.532 vs. 0.852), the t-values ​​for Serbia belong to the critical area in both sectors, while in the EU the t-values ​​for the viticulture sector do not belong to the critical area areas. The F-test values ​​showed that the fitted model is significant at the 0.05 significant level for both observation areas. An analysis of the presence of multicollinearity in variable variables was also conducted, and the results showed that there is a weak multicollinearity originating from the value of viticulture production.
Keywords: Gross domestic product (GDP), GVA, intermediate consumption, agricultural output, permanent crops